Nephronophthisis due to a novel DCDC2 variant in a patient from African‐Caribbean descent: A case report. Issue 3 (10th December 2019) - Slater, Brady; Bekheirnia, Nasim; Angelo, Joseph; Bi, Weimen; Braun, Michael C.; Bekheirnia, Mir Reza
Abstract: Nephronophthisis‐19 (NPHP19) due to truncating mutations in the DCDC2 gene has only been described previously in two patients. We describe a new case in a patient from the island country of Saint Vincent and the Grenadines, in the West Indies. This condition is a renal‐hepatic ciliopathy with phenotypic characteristics that include hepatosplenomegaly, hepatic fibrosis with bile cholestasis, increased kidney echogenicity, and end‐stage renal disease.Here, we report a 13‐year‐old African‐Caribbean female with areas of absence of heterozygosity suggesting parental consanguinity or identity by decent due to the founder effect, harboring a novel homozygous pathogenic variant (c.383C>G, p.S128*) in exon 3 of DCDC2 . Her phenotype is consistent with the other two known cases of NPHP19, however, this patient also presents psychiatric symptoms. These psychiatric findings were not present in the first two documented cases, and we discuss possible etiologies of these symptoms. Our study presents the first patient from the West Indies with NPHP19, and also highlights the need to investigate the frequency of pathogenic variants within at‐risk populations.